Sertraline Treatment of Nonresponders to Extended Cognitive-Behavior Therapy in Pediatric Obsessive-Compulsive Disorder - Skarphedinsson, Gudmundur (J Child Adolesc Psychopharmacol, 2015)
Objective: The purpose of this study was to investigate the effect of sertraline (SRT) in children and adolescents with obsessive-compulsive disorder (OCD) who did not respond to two consecutive courses of cognitive-behavior therapy (CBT). Methods: Observational study with 11 participants (males, n=6), 7–17 years of age with Diagnostic and Statistical Manual of Mental Disorders, 4th ed. (DSM-IV) primary OCD. All had received 14 plus 10 sessions of CBT over the course of 218–532 days (mean=342.2, SD=85.5). Outcome measures were mean reduction of the Children's Yale-Brown Obsessive Compulsive Scale (CY-BOCS) total score and adequate clinical response (CY-BOCS<16). All participants received SRT (maximum dose 200 mg/day). The study was a part of the Nordic Long-Term OCD Treatment Study (NordLOTS). Results: Participants were treated with SRT over 72–300 days (mean=164.2, SD=68.3). The mean CY-BOCS score was reduced from 21.5 (SD=2.6) to 17.5 (SD=3.3). Only three participants obtained adequate clinical response (27.2%), and only two obtained >25% CY-BOCS total score reduction (close to 50%). Conclusions: A clinical response in approximately one third of the participants suggests that SRT treatment might be beneficial to a minority of patients who have consistently failed CBT.